Asuhan Keperawatan Pada Tn.J Dengan Demam Thypoid Di Ruangan Muzdalifah Rumah Sakit Aisyiyah Kota Pariaman - Rice Jesika Aulia; Mike Asmaria; Hilma Yessi; Kheniva Diah Anggita (CV. ITTC INDONESIA, 2026)
Typhoid fever is an intestinal disease that occurs suddenly due to infection with the Salmonella typhi bacterium. According to the WHO, approximately 81% of people contract typhoid fever. Based on data obtained from Aisyiyah Pariaman Hospital, typhoid fever ranked 4th out of the 10 most common diseases at Aisyiyah Pariaman Hospital in 2024, with 262 cases of typhoid fever in the Muzdalifah ward. The objective of this study is to provide nursing care for patients with typhoid fever. The case study method was used, based on data obtained through observation, interviews, physical examinations, and documentation. The study was conducted in the Muzdalifah Ward of Aisyiyah Hospital in Pariaman from September 19 to 23, 2025, involving one patient, Mr. J. The study identified the following nursing issues: hyperthermia, nausea, sleep disturbances, risk of nutritional deficit. The evaluation results and implemented interventions showed that nausea and the risk of nutritional deficiency were resolved by the 4th day, while hyperthermia and sleep disturbances were resolved by the 5th day. In this case study, it is hoped that the patient and family will increase their knowledge of personal hygiene and maintain their health to avoid diseases, particularly typhoid fever.